(untitled) (Experimental biology, 2021)
The article describes the density, number and age spectrum of the rare endemic medicinal species Adonis tianschanica Lipch (Adolf). 3 populations of the species were studied. The first population was taken from the Kegen Pass, and 2 cenopulations of the species were found. The second population was found in the Tekeli gorge of Dzungarian Alatau and 2 cenopopulations of the same species as in 1 population were studied accordingly. The third population is between the villages of Saryjaz and Kainar, Terskey Alatau. A total of 3 populations and 5 coenopopulations were found and studied. Given the global nature of the problem of biological diversity, the protection of not only individual species, but also a number of unique plant communities, their diversity and stability are important conditions for optimal environment. A small part of associations is to some extent aggravated in nature reserves or protected areas, but there is no general reference list of endangered and rare plant communities and their protection is very important for the future. For all coenopopulations, accounting areas of 1m2 were built, the number of species and age composition were calculated according to the method of A. A. Uranov. In addition, the average density of individuals of the Adonis tianschanica Lipch (Adolf). type was calculated. A map has been constructed for the regions where three populations of the species are located (in Almaty region conditions). The space image was also used depending on the meeting point of coenopopulations (by geographical coordinates). Graphs are compiled for the age composition of coenopopulations of the Adonis tianschanica Lipch (Adolf) type, and the current state of abundance, density, and age composition is estimated for 3 populations of the species. Key words: Adonis tianschanica Lipch (Adolf), endem, coenopopulation, age composition, Dzungarian Alatau, Terskey Alatau.